Long-term trajectory of cognitive performance in people with bipolar disorder and controls: 6-year longitudinal study. Issue 4 (18th July 2021) - Sparding, Timea; Joas, Erik; Clements, Caitlin; Sellgren, Carl M.; Pålsson, Erik; Landén, Mikael
Abstract : Background: Cross-sectional studies have found impaired cognitive functioning in patients with bipolar disorder, but long-term longitudinal studies are scarce. Aims: The aims of this study were to examine the 6-year longitudinal course of cognitive functioning in patients with bipolar disorder and healthy controls. Subsets of patients were examined to investigate possible differences in cognitive trajectories. Method: Patients with bipolar I disorder ( n = 44) or bipolar II disorder ( n = 28) and healthy controls ( n = 59) were tested with a comprehensive cognitive test battery at baseline and retested after 6 years. We conducted repeated measures ANCOVAs with group as a between-subject factor and tested the significance of group and time interaction. Results: By and large, the change in cognitive functioning between baseline and follow-up did not differ significantly between participants with bipolar disorder and healthy controls. Comparing subsets of patients, for example those with bipolar I and II disorder and those with and without manic episodes during follow-up, did not reveal subgroups more vulnerable to cognitive decline. Conclusions: Cognitive performance remained stable in patients with bipolar disorder over a 6-year period and evolved similarly to healthy controls. These findings argue against the notion of a general progressive decline in cognitive functioning in bipolar disorder.